Terahertz Transmission‐Type Metasurface for the Linear and Circular Polarization Wavefront Manipulation. Issue 8 (1st June 2022) - Li, Jun; Cheng, Yongzhi; Li, Xiangcheng
Abstract: A transmission‐type metasurface (MS) based on the combined geometric and transmission phase is proposed and investigated here numerically, which can achieve independently manipulation of the circular polarization (CP) and linear polarization (LP) wavefront at terahertz (THz) region. The unit‐cell of the proposed MS is composed of the dielectric substrate sandwiched with the bilayered inner centrosymmetric‐notched‐elliptic (CNE), outer C‐shaped, and single‐split‐ring (SSR) structures. The proposed MS can convert the normal incident LP wave to its orthogonal one at the lower frequency ( f 1 = 0.68 THz) after transmission and left‐handed circular polarization to the transmitted right‐handed circular polarization wave or vice versa at the higher frequency ( f 2 = 1.34 THz). The full 2π phase shifts of the both transmitted LP and CP waves can be realized independently and simultaneously by varying the opening and orientation angles of the outer SSR structure based on the transmission phase and the orientation angle of the inner CNE structure based on geometric phase, respectively. As proofs of concept, anomalous refraction, planar focusing, and vortex beam generation for both LP and CP waves are demonstrated numerically. These findings show great potential applications in imaging and communication systems, providing new possibilities to develop multifunctional THz device for both LP and CP waves. Abstract : A transmission‐type metasurfaces (MSs) at terahertz (THz) region is proposed. The MS can convert the linear polarization (LP) and circular polarization (CP) wave to its orthogonal ones at 0.68 and 1.34 THz after transmission. The full 2π phase shifts of the LP and CP waves can be realized independently based on the transmission and geometric phase. As proofs of concept, anomalous refraction, focusing, and vortex beam generation can be achieved.